Cases on global leadership in the contemporary economy - Chirino-Klevans, Ivonne, 1965- (Advances in educational marketing, administration, and leadership (AEMAL) book series., 2019)
"This book focuses on cases that present scenarios of organizations or individuals who are immersed in environments that are impacted by cultural factors. It involves aspects related to leadership, management, finance, human resources, accounting but all will focus on skills related to global leadership"--